PROFITS IN THE STEEL INDUSTRY. - Hartzell, Elmer (The Accounting Review, 1934)
Abstract The data to be presented will, first, give information concerning the trend of profits in the steel industry and, second, information concerning the manner in which profits vary with changes in the size of the corporations in which production is carried on. Two conclusions of general import will be brought out, one of which indicates that profits in the steel industry, the trend of which has been downward, have been moderate, the other of which points to the conclusion that the optimum size of a corporation is a function of the total economic situation, that is, it is a variable. The point of departure will in each instance be a brief reference to some accredited opinion. The data in the first section of the paper which deals with the trend of profits, is that of the United States Steel Corp. The second section considers the way in which rationality may be given to the belief that large industrial units are productive of lower production costs, when at the same time it is acknowledged that many relatively small firms report higher rates of earnings.